2010
DOI: 10.1063/1.3486687
|View full text |Cite
|
Sign up to set email alerts
|

Full spin switch effect for the superconducting current in a superconductor/ferromagnet thin film heterostructure

Abstract: Superconductor/ferromagnet (S/F) proximity effect theory predicts that the superconducting critical temperature of the F1/F2/S or F1/S/F2 trilayers for the parallel orientation of the F1 and F2 magnetizations is smaller than for the antiparallel one. This suggests a possibility of a controlled switching between the superconducting and normal states in the S layer. Here, using the spin switch design F1/F2/S theoretically proposed by Oh et al. [Appl. Phys. Lett. 71, 2376], that comprises a ferromagnetic bilayer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 17 publications
4
64
0
6
Order By: Relevance
“…Based on the unique properties of S/F hybrids, several kinds of device physics were proposed such as proximity-effect superconducting spin-switching [13,14,15,16,17] and Josephson current switching [18,19,20] actuated by an external magnetic field. Very recently, magnetic-field-controlled superconductivity switching in the S/F proximity systems [21,22,23,24,25] and the Josephson current switching in the S/F/S junctions [26,27] were demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the unique properties of S/F hybrids, several kinds of device physics were proposed such as proximity-effect superconducting spin-switching [13,14,15,16,17] and Josephson current switching [18,19,20] actuated by an external magnetic field. Very recently, magnetic-field-controlled superconductivity switching in the S/F proximity systems [21,22,23,24,25] and the Josephson current switching in the S/F/S junctions [26,27] were demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The latter construction should be operational upon application of a small external magnetic field. Many experimental works were performed to confirm this effect for the S/F systems with a good contact between metallic F and S layers made of ordinary metals and standard ferromagnets (see, e.g., recent reviews [6]), the full switching between the superconducting and normal states has been realized only in a few cases [7,8] because ∆T c was usually smaller than the width of the superconducting transition δT c .Very recently, Singh et al reported [9] the observation of a colossal triplet spin-valve effect for the S/F1/N/F2 structure made of amorphous MoGe, Ni, Cu, and CrO 2 as the S, F1, N, and F2 layers, respectively. This structure demonstrated variation of T c by ∼ 1 K when changing the relative alignment of the two F layers.…”
mentioning
confidence: 99%
“…The latter construction should be operational upon application of a small external magnetic field. Many experimental works were performed to confirm this effect for the S/F systems with a good contact between metallic F and S layers made of ordinary metals and standard ferromagnets (see, e.g., recent reviews [6]), the full switching between the superconducting and normal states has been realized only in a few cases [7,8] because ∆T c was usually smaller than the width of the superconducting transition δT c .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an alternative F1/N/F2/S design of the superconducting spin valve [36] attracted much attention [37][38][39] because of possible high sensitivity of the superconducting T c to generation of the long-range triplet component of superconducting pairing [40,41]. Indeed, recent calculations have shown [42] that not only the "direct switching" ( ) [42], which can be most spectacularly detected as a reentrant behavior of superconductivity as a function of the angle between magnetic moments of the F1 and F2 ferromagnetic layers.…”
Section: Other Possible Design Of Superconducting Spin Valve -"Triplementioning
confidence: 99%